Social Studies Education as a Strategy in Building Anti-Corruption and Anti-Drug Character in Junior High School - Sumantri Sumantri; Hadi Wiyono; Nurhesti Nurhesti (STKIP Taman Siswa Bima, 2023)
This research aims to build Anti-Corruption and Anti-Drug characters through the learning of Social Science in junior high schools. Corruption and drug abuse are serious problems that threaten the progress and sustainability of a country. Therefore, it is important to involve the younger generation in efforts to prevent corruption and drug abuse from an early age. IPS learning is one of the ways to shape Anti-Corruption and Anti-Drug characters. Through IPS learning, a more strategic approach can be taken to build these characters by instilling values of integrity, justice, and social responsibility that are crucial in combating corruption and drug abuse. Additionally, the use of participatory learning methods such as group discussions, simulations, and case studies can enhance students' understanding and awareness of corruption and drug-related issues. In conclusion, this research provides an important contribution to the efforts of preventing corruption and drug abuse by engaging the younger generation in positive social change. The implications of this research can be used as a guide for educators in designing effective learning strategies to build Anti-Corruption and Anti-Drug characters in schools.